Análise do potencial de crescimento das exportaç\~oes agropecuárias Brasileiras nos mercados dos Estados Unidos e da Índia - Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– United States and India represent trade partners with strong demand for Brazilian food or interesting potential for future business. Here the objective was to verify the importance and potential in USA and Indian markets for Brazilian agricultural exports. Results based on identifying products in which USA or India were leader or intermediate markets in buying Brazilian agricultural exports during the seventeen last years. In general terms, for USA the major part of identified products are products already processed (animal or vegetable fats and oils, products of food industries, and products of chemical industries). Moreover, in the products in which USA were an intermediate market, grapes, bovine meat preparations, and gross sugar cane deserve attention. At the same time, India demands a smaller number of Brazilian agricultural products. This result shows the more potential profile of this country. Special highlight must be done to gross sugar cane, identified for both countries.
Keywords: F14; Q11; Q17; 330; farming and castle raising; exports; Brazil; United States of America; India